A study of perceptions, attitudes and knowledge as it pertains to susceptibility to HIV/AIDS among grade 11 pupils in Grahamstown - Mdziniso, Nompumelelo B (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
HIV/AIDS has emerged as the leading cause of death in South Africa, with young people being the most affected. Awareness of HIV/AIDS is quite high, yet prevalence rates have not stabilised and are still climbing. Lack of sexual behavioural change among young people is a major factor which explains why prevalence rates are still on the increase among this population. Sexual behaviour change is influenced by perceptions and attitudes, most notably perceived susceptibility. Information on the psychological factors that affect perceived susceptibility can provide an important base for the development of programmes aimed at reducing further transmission among young people. A survey, using a self-administered, anonymous questionnaire with close-ended questions to collect data, was conducted among Grade 11 learners (n = 318) in Rini, Grahamstown, South Africa. One of the constructs (namely Perceived Susceptibility) in the Health Belief Model informed the data collection. The data generated were first analysed descriptively, providing percentages for responses. Secondly cross-tabulations were calculated. The results showed that knowledge about HIV/AIDS is sufficient, young people receive accurate and non-conflictual messages about sex and HIV/AIDS, they are not discriminatory towards People Living With HIV/AIDS, they have adequate access to healthcare and their perceived susceptibility to HIV/AIDS is high. All these are factors which are favourable and conducive for positive sexual behavioural change. However, the study also found that there was little behaviour change among young people especially regarding regular condom use and decreased sexual activity.
Keywords: AIDS (Disease) -- Social aspects -- South Africa -- Grahamstown; HIV infections -- Social aspects -- South Africa -- Grahamstown; AIDS (Disease) in adolescence -- South Africa -- Grahamstown -- Attitudes; Youth -- Sexual behavior -- South Africa -- Grahamstown